Physiological responses to front crawl intermittent incremental protocols with different step lengths - de Jesus, Ke.; de Jesus, Ka.; Sousa, J.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Sports Science & Medicine, 2012)
The use of the intermittent incremental protocol of 200 m step length (2-3min depending on the swimming intensity), conducted in ecological conditions, is not new for swimmers evaluation and training control. Studies that used it provided an important contribution regarding swimmers physiological characterization through the assessment of oxygen uptake (VO2), blood lactate concentrations ([La¯]) and energy expenditure. However, steps higher than 4min duration have been suggested to be proper for VO2 stabilization and to the [La¯] better express its muscular production. We aimed to compare three variants of a front crawl intermittent incremental protocol with different step lengths to assess traditional and recently proposed relevant physiologic parameters. Methods: Six trained swimmers (21.0 ± 2.06 years, 73.8 ± 4.02kg and 1.82 ± 0.05m) performed three randomized repetitions of a front crawl intermittent incremental protocol until exhaustion. Each variant had different step lengths (200, 300 and 400m), increments of 0.05m/s and 30s intervals between steps (24h were respected between variants). VO2 was collected breath-by-breath (averaged 10s) using a K4b2portable gas analyser connected to the new AquaTrainer respiratory snorkel (Cosmed, Italy). For the data analysis, it was selected, in each variant, the step where VO2max occurred, and compared the values of VO2max, maximal ventilation (VEmax), maximal VO2 efficiency (OUE, VO2/VE), and [La¯]max. Descriptive statistics and Friedman`s test (p = 0.05) were calculated. Results: Median and interquartil range for VO2max, VEmax, OUE and [La-] for 7x200, 300 and 400m were, respectively: 56.05 (51.9-71.3), 54.3 (51.1-59.9) and 51.6 (51.6-55.3) ml/kg·min (with differences between variants, p < 0.01), 140.8 (120-149), 138.9 (100-167) and 132.5 (101-157) l·min-1, 29.8 (26.3-34.8), 29.9 (23.5-37.4) and 29.2 (24.8-34.7)ml/l, and 8.1 (7.9-10.9), 8.2 (8-8.8) and 8.5 (7.8-10.8)mmol/l. Conclusions: The values of VEmax, OUE and [La-] were similar independently of the step lengths used. However, the variant of the incremental protocol using 400m step length seems to underestimates the VO2max values, suggesting that the 7x400m incremental protocol might not be the ideal one to use when the aim is to characterize the swimmers maximal aerobic power. So, coaches and researchers should use incremental protocols with short step durations, particularly of 200 m, once the test will be simpler and faster, swimmers will be easier motivated to perform a maximal effort, and the final results will not be negatively affected by its shorter step length